Systematic Literature Review: Media Pembelajaran Matematika pada Materi Luas Bangun Datar di Sekolah Dasar - Yumnaa Humairo; Trimurtini, Trimurtini (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to systematically examine the use of learning media for the area of flat shapes in upper elementary school. The method used is a Systematic Literature Review (SLR) of 21 articles from national journals accredited by SINTA 3–5 published between 2023 and 2025, and 12 articles were selected that met the criteria. The results of the study indicate that the learning media used are divided into three categories: concrete media, digital media, and a combination of both. Concrete media such as tangrams, geoboards, SMARD cards, and true or false cards have proven effective in improving learning outcomes through direct experience that is in accordance with the concrete operational stage according to Piaget's theory. Digital media such as Wordwall-based E-LKPD, the Genially application, and augmented reality provide visual and interactive learning experiences that support conceptual understanding in accordance with Edgar Dale's Cone of Experience theory. Combined media such as KOMET-QR combines concrete and digital elements to provide contextual and comprehensive learning. The results of the study conclude that the selection of appropriate and varied learning media, in accordance with student characteristics and pedagogical principles, can effectively improve the quality of mathematics learning in elementary schools. Educators are expected to be able to explore and develop innovative and effective learning media that are adapted to student needs and developments in educational technology.